SYNERGY OF TOURISM OFFICE IN MANAGING TOURIST DESTINATIONS IN SOLOK CITY - Nabila Audrey Sylindra; Kiki Rizki Makiya; Moch. Nur Syamsu; Agung Yuliyanto Nugroho (PT. Jurnal Center Indonesia Publisher, 2025)
Tourism plays a strategic role in supporting regional economic growth, including in Solok City, which has rich natural and cultural tourism potential. However, the optimization of destination management in this city faces several challenges, such as limited human resources, inadequate infrastructure, low community awareness, and insufficient promotion strategies. This study aims to analyze the role of the Tourism Office in optimizing destination management, identify influencing factors, and formulate strategic efforts towards sustainable tourism management. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with stakeholders (government, private sector, community, academia, and media), and document studies. The results show that the Tourism Office of Solok City plays a key role in four main functions: planning, implementation, coordination, and evaluation. Programs conducted between 2021 and 2024 include destination development, tourism promotion, human resource capacity building, and cross-sector partnerships. Internal and external factors such as budget constraints, infrastructure limitations, community participation, and destination competitiveness influence management effectiveness. The implementation of Good Governance principles participation, transparency, accountability, and efficiency along with Destination Management approaches, has guided policy and program implementation. However, some aspects, particularly cross-sectoral integration and innovation in tourism promotion, still need improvement. This study concludes that strengthening stakeholder synergy and enhancing institutional capacity are crucial for optimizing sustainable destination management in Solok City